Molecular determinants of human renal clear cell carcinoma cancer risk - Rani, Kumari Vandana (2017)
Hypoxia-related pathways play key roles in the mechanism that lead to development of acute kidney injury (AKI) and clear cell renal carcinoma (ccRCC). This dissertation used a pig model of AKI and a mouse model of ccRCC to compare the molecular mechanisms of these two disease processes to determine whether AKI may contribute to ccRCC risk. In the present study we first used next generation sequencing to identify single nucleotide variants (SNVs) and splicing effects in the mouse TRACK ccRCC model relative to wild-type control mice. This analysis identified multiple variants in TRACK mice, including an intronic variant in the NDUFA4L2 locus predicted to alter splicing and a coding variant in the CES3 gene. We analyzed the prevalence of mutations and differential expression in these genes in human ccRCC genomic data. Our study has identified a novel CES3 mutation in mice over-expressing HIF-1α and several other genes like Hilpda, Zbtb38, Cdc58, Plekhm2 and Aldoa illustrated splice junctions variations. The association of these genes with ccRCC have to be investigated. Our results showed over expression of MYC and ANXA2 gene in both AKI and ccRCC model and in human ccRCC as well. Secondly, we used RNA sequencing to compare the transcriptome of kidney samples from the pig and mouse models of AKI and ccRCC respectively. This analysis identified a network of genes deregulated in both AKI and ccRCC. The expressions of these genes were further analyzed in the cancer genome atlas patient ccRCC (KIRC) RNA sequencing dataset. Collectively these analyses have identified increased expression of MYC as an important driver of the pathogenic processes in both AKI and croc. Further retrospective clinical studies are now warranted to investigate whether AKI predisposes to ccRCC in people.